Bioremediation of vegetable oily ballast wastewater under temperate condition using Antarctic bacteria - Abubakar, Maryam (2017)
Spills of vegetable oily waste especially palm oil as a result of ballast water discharge from vegetable oil tankers in temperate waters are of environmental concern because they cause serious effects on marine life and coastal environments. The ongoing reclassification of oil palm ballast waste as a hazardous substance by the European Union will seriously affect the Malaysian economy. Biodegradation by indigenous cold-tolerant microorganisms is an important and potentially remediating process solving this current problem. This study aims to investigate the biodegradability of vegetable oil (palm oil) under the influence of a cold-tolerant bacteria (Rhodococcus erythropolis ADL36) previously isolated from Antarctica. The strain was cultured at different oil concentrations, temperature, pH, salinity, and inoculum size under simulated conditions of oily ballast waste water. Furthermore, the influences of the independent variables were optimised using response surface methodology (RSM). A Plackett-Burman screening was carried out prior to RSM. Three factors namely temperature, oil concentration and inoculum size appears to be the most significant factors among the five while two factors; pH and salinity show non-significant effect on the degradation of palm oil. The results of the research have shown that maximum growth and biodegradation occurred at 1% (v/v) of the oil, at 25oC, pH 6.8, 2% of NaCl and an inoculum size of 5% (v/v) after OFAT. The difference in the peaks of the oil component was seen in the GCMS result. Moreover, the results of RSM showed that oil concentration, temperature and inoculum size showed significant effects on the biodegradation of the oil. Out of the eight primary models utilize, the modified Gompertz model was the best in modeling the bacterial growth. Based on the growth rate constants obtained from the primary modelling, a secondary modelling was carried out using various models such as Luong, Yano, Tessier-Edward, Aiba, Haldane, Monod, and Han and Levenspiel. The best model was Haldane giving the calculated value for the Haldane’s constants such as maximal growth rate (max), half saturation constant for maximal growth (Ks) and growth inhibition constant (Ki) tolerated were 0.74±0.12 day-1, 1.23±0.14 palm oil (% v/v), and 3.12±0.16 palm oil (% v/v), respectively. In conclusion, the results indicated the efficiency of such a system as a potential treatment for oily ballast wastewater (vegetable oil).